2020
DOI: 10.1074/jbc.ra119.011239
|View full text |Cite
|
Sign up to set email alerts
|

The pentose phosphate pathway of cellulolytic clostridia relies on 6-phosphofructokinase instead of transaldolase

Abstract: The genomes of most cellulolytic clostridia do not contain genes annotated as transaldolase. Therefore, for assimilating pentose sugars or for generating C5 precursors (such as ribose) during growth on other (non-C5) substrates, they must possess a pathway that connects pentose metabolism with the rest of metabolism. Here we provide evidence that for this connection cellulolytic clostridia rely on the sedoheptulose 1,7-bisphosphate (SBP) pathway, using pyrophos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…For example, formation of valine from 2 pyruvate then requires 3 PP i . PP i is even required for the formation of pentose-phosphates from fructose-6P and triose-phosphate due to an alternative pentose phosphate cycle resulting from the absence of transaldolase ( 35 , 36 ). where F6P is fructose 6-phosphate, FBP is fructose 1,6-bisphosphate, C3P is triose phosphate, C4P is erythrose 4-phosphate, C5P is pentose 5-phosphate, C6P is hexose phosphate, C7P is sedoheptulose 7-phosphate, and SBP is sedoheptulose 1,7-bisphosphate.…”
Section: Discussionmentioning
confidence: 99%
“…For example, formation of valine from 2 pyruvate then requires 3 PP i . PP i is even required for the formation of pentose-phosphates from fructose-6P and triose-phosphate due to an alternative pentose phosphate cycle resulting from the absence of transaldolase ( 35 , 36 ). where F6P is fructose 6-phosphate, FBP is fructose 1,6-bisphosphate, C3P is triose phosphate, C4P is erythrose 4-phosphate, C5P is pentose 5-phosphate, C6P is hexose phosphate, C7P is sedoheptulose 7-phosphate, and SBP is sedoheptulose 1,7-bisphosphate.…”
Section: Discussionmentioning
confidence: 99%
“…For bacteria, the first proof of the so-called SBPP was provided for two cellulolytic clostridia. Koendjbiharie et al [28] showed that the PPi-PFKs of Pseudoclostridium thermosuccinogenes and Hungateiclostridium thermocellum can convert S7P to S-1,7-bP and proposed that the FBP aldolase is responsible for the cleavage of S-1,7-bP, which was already shown in plants using the Calvin cycle [46,47], in Methylococcus capsulatus [48] and in Mycobacterium smegmatis [49]. Furthermore, the phosphorylation of S7P by PPi-PFKs was already demonstrated for Methylococcus capsulatus [50], Enterococcus faecalis [51], and Methylomicrobium alcaliphilum [52].…”
Section: Discussionmentioning
confidence: 99%
“…One potential pathway to circumvent the reaction of the transaldolase in P. copri is the combined catalysis of a phosphofructokinase (PFK) that could be able to phosphorylate sedoheptulose 7-phosphate (S7P) and an aldolase that cleaves sedoheptulose 1,7-bisphosphate (S-1,7-bP) to erythrose 4-phosphate (E4P) and dihydroxyacetone phosphate (DHAP) [28]. Strikingly, the genome of P. copri codes for two PFKs, from which one is predicted to be ATP-(ATP-PFK; PRE-VCOP_04138; EC 2.7.1.11) and the other pyrophosphate (PPi)-dependent (PPi-PFK; PREVCOP_03899; EC 2.7.1.90) ( Table 1).…”
Section: Bioinformatic Prediction Of the Pentose Metabolism Of P Coprimentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Tal has been shown to play a key role in PPP in some bacteria but not others (Nakahigashi et al, 2009;Koendjbiharie et al, 2020). Hence, either Francisella possesses a functional paralog lacking significant amino acid sequence similarity with Tal, or another enzyme known to play a different role, may also be capable of compensating, under certain metabolic conditions, for the absence of transaldolase.…”
Section: Cross-talk Between Ppp and Other Metabolic Pathwaysmentioning
confidence: 99%